Increasing Amil and Nadzir’s Capacity through Management Tools Training in ZISWAF Management - M Usman; lila pangestu hadiningrum; Roykhatun Nikmah; Ning Karnawijaya; Betty Eliya Rochmah (Universitas Muhammadiyah Palembang, 2023)
Management Tools training for ZISWAF Management is used to assist performance, especially for ZISWAF Institution practitioners, namely amil and nadzir in managing their activities. This program focuses more on improving the skills of amil and nadzir in managing ZISWAF by using management tools tailored to the needs of the institution. Community Based Research is a PKM method by dividing training stages; Facilitation, communicating with adult learning, communicating with various experiences (experiential learning) and developing educational programs (educational program development). This training was effective as an effort to increase the capacity of Amil and Nadzir, seen from the conditions before and after the training practice which showed a quite significant percentage increase, namely seen from the indicators of implementing the training program from non-existent to existing, module socialization (50%), training (60%), awareness as well as community response (30%.). These results show that this activity has met the specified specifications (quality), within the specified cost (C), time (T) limits, and resource utilization can be carried out effectively and efficiently. The implication is that ZISWAF institutions need to be synergistic and sustainable.